Stimulation of n−π∗transition of g-C3N4 through ZnAl-layered double hydroxide for solar light assisted phenol degradation. (15th March 2020) - Tripathi, Alok; Narayanan, Sheeba
Abstract: The structural framework of graphitic carbon nitride (g-C3 N4 ) was tuned with Zinc Aluminium layer double hydroxide (ZnAl-LDH), and its photocatalytic activity was investigated through solar light assisted phenol degradation of real effluent. The modified g-C3 N4 (70%g-C3 N4 /ZnAl-LDH) possess more efficient inhibition of electron and hole pairs resulting in red shifting of absorption edge which stimulates the n − π ∗ electronic transition. Morphological studies confirm that the LDH flocks consistently covered the g-C3 N4 sheets affirming a substantial collaboration between two-layered material through electrostatic interlink and charge exchange synergy. Furthermore, 70%g-C3 N4 /ZnAl-LDH have an increased surface area of 26.292 m 2 /g and a reduced bandgap energy of 2.55 eV, which results in enhanced photocatalytic activity. The results of experimental study indicate that after 300 min of illumination in slight acidic condition, with 1.5 g/L chemical oxidant dose at 3 L/h reactor flowrate, 70%g-C3 N4 /ZnAl-LDH exhibits 79.35% degradation of phenol, and under same conditions, g-C3 N4 confers 61.25% degradation. Graphical abstract: Image 1 Highlights: Structural framework of g-C3 N4 is tuned with Zinc Aluminium layer double hydroxide (ZnAl-LDH) to stimulate its n − π ∗ electronic transition. The performance of ZnAl-LDH modified g-C3 N4 has been investigated to treat real industrial effluent under natural solar light.